1997
DOI: 10.1021/om960799g
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrization of Phenylmercuric Hydroxides by the Action of Nickel(II) and Cobalt(II) Acetylacetonates. Isolation and Structural Characterization of an Intermediate in This Reaction

Abstract: The complex adducts [M(acac)2(PhHgOHgPh)]2 (M = Co, Ni) have been obtained by incorporation of PhHgOH into the coordination sphere of M(acac)2 at ambient temperature. The X-ray crystal structure of [Ni(acac)2(PhHgOHgPh)(Et2O)]2 (1c) reveals a dimeric nickel complex coordinated by the acetylacetonate oxygen and the bridging oxygen of bis(phenylmercuric) oxide. Refluxing a THF solution of compound 1c gave diphenylmercury, HgO, and Ni(acac)2(THF)2. With PhHgOH or PhHgSH the symmetrization reactions also occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The solid-state structure for octahedral complexes of the type [M(acac) 2 (L)] 2 (M = Ni, Co; acac = acetylacetonate; L = alcohols, amines) have recently been reported (Kessler et al, 2003;O'Connor et al, 1984;He, Yao, Luo, Zhang, Lui, Zhang & Wu, 2003;Doring et al 1997). Such complexes are potential precursors for chemical vapor deposition to form ceramic oxides, for example NiO, which is used in ceramic material applications.…”
Section: Commentmentioning
confidence: 99%
“…The solid-state structure for octahedral complexes of the type [M(acac) 2 (L)] 2 (M = Ni, Co; acac = acetylacetonate; L = alcohols, amines) have recently been reported (Kessler et al, 2003;O'Connor et al, 1984;He, Yao, Luo, Zhang, Lui, Zhang & Wu, 2003;Doring et al 1997). Such complexes are potential precursors for chemical vapor deposition to form ceramic oxides, for example NiO, which is used in ceramic material applications.…”
Section: Commentmentioning
confidence: 99%
“…Bloodworth reports a true PhHgOH, which is dehydrated to a stable (PhHg) 2 O, based on spectroscopic and gravimetric data 5 . More recently Doring et al have demonstrated that Ni(acac) 2 catalyses the disproportionation reaction of PhHgOH to Ph 2 Hg, HgO and H 2 O, and they isolated a dimeric nickel complex with a bridging (PhHg) 2 O ligand which may be an intermediate in the process 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[20,50] The Hg À O distance for 3 is 3.019 (6) , which is shorter than that in (14) ]. [51] A survey of the literature reveals that 2 and 3 are rare examples of structurally authenticated Cd and Hg complexes to feature a diethyl ether molecule coordinated to the metal. [48,51] The two metal-substituted aryl rings are oriented at angles of 63.00(13)8 (2) and 62.1(3)8 (3) from each other.…”
Section: Full Papermentioning
confidence: 99%
“…[51] A survey of the literature reveals that 2 and 3 are rare examples of structurally authenticated Cd and Hg complexes to feature a diethyl ether molecule coordinated to the metal. [48,51] The two metal-substituted aryl rings are oriented at angles of 63.00(13)8 (2) and 62.1(3)8 (3) from each other. The terphenyl ligands in 2 and 3 are both arranged in a synconfiguration with all of the flanking naphthyls having their outer phenyl rings turned away from the metal.…”
Section: Full Papermentioning
confidence: 99%